SPECIFIC FEATURES OF NATURAL GAS SUPPLY IN SOME EU COUNTRIES - Tünde Köteles (Acta Tecnología, 2018)
The monthly gas balances for Hungary and for five other EU Member States were investigated between 2008 and 2017. For the analysis, monthly data available in the EUROSTAT database [nrg_103m] was used to ensure that the data for the different countries are comparable. Time charts for each country were used with a three-figure set of figures. For each country studied, the first member of the graph group shows the seasonal changes in the use of natural gas for the period 2008-2017. The timely changes in the liability side of domestic production and net imports, the domestic user's use of the user's page, are time-consuming, and the storage activity is illustrated by the quantities extracted from the containers. In the second graph of the group of figures, the monthly opening and closing stock of the gas stored in the given country / country group, as well as the change in the net import, are shown. Finally, the third figure illustrates the change in inventory variability for the gas year from 1 April to 31 March. The authors conducted the analysis for the EU-27, Hungary, Austria, France, Italy and the Czech Republic, and their findings were formulated for the listed countries.